First Report for Painted Globular Frog Uperodon taprobanicus in North Bastar Kanker District of Chhattisgarh, (India) - Pandey, Chiranjeev; Thiske, Sanjay; Bhatia, Gurprit Singh; Ali, Majid; Damle, Kiranlata (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The North Bastar Kanker is full of natural wealth where different types of species are found every year, out of which new species are found the Painted Globular Frog (Uperodon taprobanicus) has been seen for the first time, according to the current study. One year of observation throughout the village badgaon near Khandi Rivershowed this species to be present in this microhabitat. The species' taxonomic validity in the area was aided by morphological and photographsanalysis that validated its identification. The known distribution range of U. taprobanicus, which was previously primarily reported in South India and Sri Lanka, is expanded by this finding. In order to shed light on the state of the species' conservation in this area, ecological characteristics like habitat choice, microhabitat usage and potential threats were also evaluated. The exploration underscores the importance of continued monitoring and conservation efforts to safeguard the diversity of amphibians in Chhattisgarh and highlights the need for further research to elucidate the ecological requirements and population dynamics of U. taprobanicus in its newly identified habitat. This species has been marked in the IUCN data and its conservation is very important in time. If we cannot conserve it, then we will eliminate this species from our ecosystem and we may see natural calamity and loss in the near future.